Yi-Qi-Jian-Pi formula ameliorates immune function in acute-on-chronic liver failure by upregulating autophagy and mitochondrial biogenesis in CD8+ T lymphocytes. (23rd May 2023) - Tang, Li; Wang, Xi; Zhao, Rong; Chen, Xiaomei; Wang, Feixia; Xia, Siwei; Xiao, Qian; Zhao, Qiang; Yang, Shiyan; Tan, Shanzhong
Abstract: Ethnopharmacological relevance: A key event in the pathogenesis of acute-on-chronic liver failure (ACLF) is the imbalance in the systemic immune response; immunosuppression in patients with ACLF contributes to poor prognosis. The Yi-Qi-Jian-Pi formula (YQJPF) may improve T lymphocyte immune function in patients with ACLF. Aim of the study: To investigate the immune mechanism of YQJPF in vivo and in vitro . Materials and methods: An ACLF rat model was established by injection of CCl4, lipopolysaccharide, and D-galactosamine. We examined the effect of different doses of YQJPF (6.43, 12.87, 25.74 g/kg) on liver injury and immune function in the ACLF rat model. Magnetic-activated cell sorting was used to sort the CD8 + T lymphocytes in the spleen for lymphocyte function detection. In primary CD8 + T lymphocytes and Jurkat cell lines, the expression of mitochondrial function and biogenesis and autophagy related markers were detected using molecular biological methods and flow cytometry analysis. Results: YQJPF improved the peripheral blood lymphocyte count and proportion of CD8 + T lymphocytes in ACLF rats, increased pro-inflammatory factors (IL-2, IFN-λ, and TNF-α), and reduced anti-inflammatory factors (IL-10 and TGF β1). YQJPF also improved metabolism and mitochondrial homeostasis in CD8 + T lymphocytes, alleviated lymphocyte immune dysfunction by promoting autophagy, upregulated mitochondrial biogenesis by promoting PGC-1α, NRF-1, and TFAM expression, and regulated the relationship between autophagy and mitochondrial biogenesis via PGC-1α. Conclusions: Our results suggest that YQJPF could improve immune function in a rat model of ACLF, possibly via affecting the homeostasis of lymphatic mitochondria in CD8 + T lymphocytes. YQJPF may enhance lymphocyte mitochondrial biosynthesis and promote lymphocyte autophagy. PGC-1α is a possible upstream regulatory target of YQJPF. Graphical abstract: YQJPF may play a role in improving lymphocyte immunosuppression by enhancing lymphocyte mitochondrial biogenesis and promoting lymphocyte autophagy. PGC-1α is a possible upstream regulatory target of YQJPF. Image 1